The Failure of Drexel Burnham Lambert: Evidence on the Implications for Commercial Banks - Benveniste, Lawrence M.; Singh, Manoj; Wilhelm, Jr., William J. (Journal of Financial Intermediation, 1993)
We argue that since bank loans and publicly traded sub-investment-grade debt, or junk bonds, are close substitutes for one another, the recent failure of Drexel Burnham Lambert created a competitive opportunity for commercial banks. Consistent with this hypothesis, we observe within the commercial banking industry a positive wealth effect associated with Drexel′s failure. The distribution of the wealth effect across commercial banks and Drexel′s investment banking rivals is consistent with the wealth effect being primarily a reflection of market expectations of a return to traditional intermediated funding of sub-investment-grade debt. Journal of Economic Literature Classification Number: G2, Financial Institutions and Services.